PENERAPAN PEMBELAJARAN BAHASA ARAB BERBASIS ALQURAN DI UMSU (Studi Kasus Pembinaan Pembelajaran Bahasa Arab di FKIP Universitas Muhammadiyah Sumatera Utara) - Ghani, Nahar A.Abdul (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2019)
The results of the study entitled "The Application of Arabic-Based Learning of the Quran at UMSU" can only be done at FKIP Muhammadiyah University, North Sumatra. This research aims to:1. conduct a preliminary study to find models used by Arabic language lecturers at UMSU. And discuss a new model. 2. Try out and improve the Arabic learning model offered. 3. Arranging lecturer manuals and textbooks as well as making Arabic-based Arabic textbooks program. This research uses quantitative methods. UMSU (Muhammadiyah University of North Sumatra), low. In general, the results of the research in the framework (percentage) through questionnaires, observations or interviews show that the difference is because students do not have the appropriate basis before entering UMSU, because as many as 115 people from 250 academics who study Arabic at the elementary level with a frequency of 55% . While others While there is learning at the level of high school and junior high school but only in public schools.